The Xenes Generations: A Taxonomy of Epitaxial Single‐Element 2D Materials - Grazianetti, Carlo; Martella, Christian; Molle, Alessandro (Physica status solidi. PSS-RRL. Rapid research letters, 2020)
Xenes are two‐dimensional monoelemental materials beyond graphene ranging from silicene through borophene and to tellurene. Allessandro Molle and co‐workers (article number 1900439) review the rise of the Xenes and classify them in two generations from its early stage up to now. The attention is specifically paid to the epitaxial methodologies for the Xene synthesis approaches and to key‐characteristics, like scalability, quality, and stability, which enable the Xenes integration into diverse nanotechnology platforms.